2021
DOI: 10.1021/acscatal.1c02495
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CO2 Electroreduction with a Monolayer Bi2WO6 through a Metallic Intermediate Surface State

Abstract: Electrocatalytic conversion of carbon dioxide to high-value fuels and chemical feedstocks represents a promising solution toward carbon neutrality. Ongoing efforts have been directed to the development of high-performance, mass production, and cost-efficient catalysts, which, in turn, requires a more precise understanding of the operando details of the catalytic interface and fine control over the reaction pathway. Here, we report that a two-dimensional (2D) monolayer Bi2WO6 with high bismuth exposure demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In experiment, 2D Bi 2 WO 6 monolayer have been successfully synthesized and applied to photocatalytic field recently. 67,68 The previous works show that 2D Bi 2 WO 6 monolayer is an indirect semiconductor with the bandgap of 2.76 eV at the HSE06 level and the CBM and VBM of Bi 2 WO 6 monolayer deducted by the vacuum energy level are −4.63 and −7.39 eV, respectively, matching those of W 4 PCl 11 monolayer with the typical band alignment of type-II heterostructure. 13,66 Thus, as shown in Fig.…”
Section: Optical Absorption and Pce For Solar Cellsmentioning
confidence: 80%
“…In experiment, 2D Bi 2 WO 6 monolayer have been successfully synthesized and applied to photocatalytic field recently. 67,68 The previous works show that 2D Bi 2 WO 6 monolayer is an indirect semiconductor with the bandgap of 2.76 eV at the HSE06 level and the CBM and VBM of Bi 2 WO 6 monolayer deducted by the vacuum energy level are −4.63 and −7.39 eV, respectively, matching those of W 4 PCl 11 monolayer with the typical band alignment of type-II heterostructure. 13,66 Thus, as shown in Fig.…”
Section: Optical Absorption and Pce For Solar Cellsmentioning
confidence: 80%
“…It can be seen from Fig. 2c that the (200) interplanar spacing of BWO in the HRTEM image is 0.273 nm, and the interplanar spacing of Au particle is 0.231 nm [31][32][33]. Additionally, the elemental mapping images (Fig.…”
Section: Structure and Composition Characterizationmentioning
confidence: 86%
“…15,16 Notably, although satisfying high Faraday efficiencies (FEs) and current densities have been achieved in the field of electrocatalytic carbon dioxide reduction to formic acid with bismuth-based materials, it is still difficult to clarify the universal determining factor (if any) for the performance of whole bismuth-based catalyst family, which is certainly beneficial to its ongoing development toward industrializa-tions. This task is made even more challenging considering the inevitable in situ structural/morphological reconstructions of the Bi-based catalysts in the electrochemical reduction of carbon dioxide under operando electrolysis conditions, 17,18 during which the phase transformation, the changes of valence state, local coordination environment, and electron-transfer behavior of catalysts all requires careful consideration. In addition to the precise in situ characterizations of the electrode materials, the correlation between these initial and operando states, if existing, is also of significant value to facilitate the advancing of future catalytic systems.…”
mentioning
confidence: 99%
“…23,24 It has been recently revealed that nonmetal bismuth materials go through an in situ structure change during the electrocatalytic process, into a metallic meta-phase with close-to-zero valence state of Bi, while much of the solid evidence indicated that such an immediate metalloid bismuth is the actual active species. 17,25,26 It is therefore interesting to notice that the asprepared metal bismuth even shows inferior performance for carbon dioxide reduction compared to other bismuth compound derivatives in an aqueous solution. Two possible reasons could contribute to this phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation